How to encourage older people to remain in paid employment - Jansz, Janis (World Safety Organization, 2011)
This article reports the findings of a focus group discussion by 33 people from 5 countries to answer the question of "How do we encourage older people to remain in paid employment?" This focus group discussion was conducted at the World Safety Organization Roundtable XIII at the request of the United Nations Economic and Social Council. The following factors were identified. Consider older people's skills and abilities, ergonomic factors and individual differences, return to work after retirement, educational needs of older employees, motivation, the role of government legislation and offering older people contract work. Recommendations based on these themes were submitted to the United Nations Economic and Social Council and are included in this article.